207-nm UV Light—A Promising Tool for Safe Low-Cost Reduction of Surgical Site Infections. II: In-Vivo Safety Studies - Buonanno, Manuela; Stanislauskas, Milda; Ponnaiya, Brian; Bigelow, Alan W.; Randers-Pehrson, Gerhard; Xu, Yanping; Shuryak, Igor; Smilenov, Lubomir; Owens, David M.; Brenner, David J. (PLOS ONE, 2016)
Background UVC light generated by conventional germicidal lamps is a well-established anti-microbial modality, effective against both bacteria and viruses. However, it is a human health hazard, being both carcinogenic and cataractogenic. Earlier studies showed that single-wavelength far-UVC light (207 nm) generated by excimer lamps kills bacteria without apparent harm to human skin tissue in vitro. The biophysical explanation is that, due to its extremely short range in biological material, 207 nm UV light cannot penetrate the human stratum corneum (the outer dead-cell skin layer, thickness 5–20 μm) nor even the cytoplasm of individual human cells. By contrast, 207 nm UV light can penetrate bacteria and viruses because these cells are physically much smaller. Aims To test the biophysically-based hypothesis that 207 nm UV light is not cytotoxic to exposed mammalian skin in vivo. Methods Hairless mice were exposed to a bactericidal UV fluence of 157 mJ/cm2 delivered by a filtered Kr-Br excimer lamp producing monoenergetic 207-nm UV light, or delivered by a conventional 254-nm UV germicidal lamp. Sham irradiations constituted the negative control. Eight relevant cellular and molecular damage endpoints including epidermal hyperplasia, pre-mutagenic UV-associated DNA lesions, skin inflammation, and normal cell proliferation and differentiation were evaluated in mice dorsal skin harvested 48 h after UV exposure. Results While conventional germicidal UV (254 nm) exposure produced significant effects for all the studied skin damage endpoints, the same fluence of 207 nm UV light produced results that were not statistically distinguishable from the zero exposure controls. Conclusions As predicted by biophysical considerations and in agreement with earlier in vitro studies, 207-nm light does not appear to be significantly cytotoxic to mouse skin. These results suggest that excimer-based far-UVC light could potentially be used for its anti-microbial properties, but without the associated hazards to skin of conventional germicidal UV lamps.